Feasibility Study of Integrated Desizing, Scouring and Bleaching of Cotton Woven Fabric with H2O2 and Investigation of Various Physical Properties with Traditionally Treated Fabric - Md. Golam Nur; M. Forhad Hossain; Mustafijur Rahman (European Scientific Journal, ESJ, 2016)
Pre-treatment plays a significant role for the successful coloration of any kind of natural textile fiber like cotton, wool, flax, silk etc. This research work overview the influence of various types of traditional preparation techniques applied on cotton fiber before coloration such as desizing, scouring and bleaching. The traditional pre-treatment processes consume plenty of environmentally unfriendly chemicals those generate pollution in the effluents. In this research work an endeavour has been made to desize, scour and bleach grey cotton woven fabric simultaneously using caustic soda and hydrogen peroxide. The physical properties like whiteness, percent loss in fabric weight, tensile strength of the treated fabric have been compared with those of the fabric treated to conventional desizing, scouring and bleaching process. It is observed that the whiteness (ready for colouration) obtained by this process is quite satisfactory. Moreover, this process has some other merits such as ecological, economical, energy conserving and time saving aspect.